Enfermeiros da área da saúde suplementar e o programa de gerenciamento da saúde de idosos: como está seu cuidar? - Osti, Andréia Veloso (2018)
The purpose of this study was to understand how a visiting nurse can appropriately orient an elderly person in the home to the point of inserting such guidelines into health and incorporating them into their daily lives , which means that the effectiveness of the results of such procedures can be ascertained. This is an exploratory-descriptive study, in a qualitative approach, whose data were collected through the application of a questionnaire based on the nursing diagnoses of NANDA International, Definitions and Classifications, included in the book Nursing Diagnostics (2012-2014). This questionnaire was completed by seven nurses who work in a private health care company that performs Chronic Disease Management for those aged 60 or over in their homes. The application of the questionnaire with 13 questions occurred twice: the first one, before the training stage, and the second, after that stage, during the first half of 2017, in the city of São Paulo. As results, it was verified the need for a more competent multidisciplinary training of nurses for health guidance to the elderly in their home, especially in the light of gerontological knowledge. The sample of this study seemed to show, through the initial frustration of its procedures, that, according to our hypothesis, a reflexive-critical reasoning about one's own actions of care was lacking, as well as a more affectionate and concentrated look at each elderly person. It would not suffice, in our view, to apply techniques with rigid protocols, which provide only punctuations to pre-defined answers, insufficient to capture the long-lived singularity; the protocols should be seen in what they are: indicators for more effective health actions. The results, in fact, attest that, affected by the gerontological training, nurses began to assume different procedures in the reception and orientation to the elderly, with these being alerted to the necessary adherence to daily habits of sustainable life